CONCEPTS, PRINCIPLES AND FEATURES OF INTERACTION OF SECURITY FORCES, JUDICIAL AND LAW ENFORCEMENT AUTHORITIES OF UKRAINE DURING THE EXECUTION OF SERVICE AND COMBAT MISSIONS TO COUNTERACT SMUGGLING - Krylovetskiy, Andriy (Honor and Law, 2022)
The issues of cooperation between the security forces, judicial and law enforcement agencies of Ukraine during the implementation of combat missions to combat smuggling were raised. It is determined that ensuring optimal cooperation between the security forces and the judiciary and law enforcement agencies of Ukraine in the performance of combat missions to combat smuggling largely depends on the correct interpretation of the category of «interaction». Terminological analysis shows that the concept of «interaction» is outwardly similar to concepts such as «coordination» and «cooperation». It is established that «coordination» and «cooperation» are components of interaction during the organization of interaction. The purpose of the article is to study modern scientific research to substantiate the concepts, principles and features of cooperation between the security forces, judicial and law enforcement agencies of Ukraine in the performance of combat missions to combat smuggling. It is established that the postulates of management theory state that the organization of interaction is a process of creating a management structure of the organization, which allows staff to unite their efforts to achieve certain goals. These elements of the organization of cooperation are the features of the interaction of security forces, judicial and law enforcement agencies of Ukraine in the performance of combat missions to combat smuggling, the effective implementation of which is based on certain principles. It is determined that today in scientific research there is a stable group of principles, the main of which in the perspective of research issues are the following: unity of purpose; delimitation of competencies; systematicity; planning; professionalism; efficiency; optimality. Regardless of the manifestations and functions of cooperation between the security forces, the judiciary and law enforcement agencies of Ukraine, they must be based on certain established principles. In addition, the current state of implementation of combat missions to combat smuggling shows that today not enough attention is paid to compliance with the principles of cooperation between security forces, judicial and law enforcement agencies of Ukraine, without which cooperation will not be effective. It is proved that the issues of interaction between the security forces, judicial and law enforcement bodies of Ukraine are regulated in general by joint orders and the interacting central executive body. But practice shows that today it is insufficient to regulate the relationship of interaction at the interagency level. In order to effectively cooperate with the security forces, judicial and law enforcement agencies of Ukraine in combating smuggling, it is necessary to develop and approve an appropriate concept of comprehensive cooperation at the state level. Areas of further scientific research will be aimed at studying the peculiarities of the interaction of the security forces, judicial and law enforcement agencies of Ukraine with the defense forces during combat missions to combat smuggling in the area of the Joint Forces operation.